Silver barb: A promising candidate for aquaculture diversification in Meghalaya hills - Singh, S Gojendro; Debnath, Chandan; Mahanta, Prasanta; Tayung, Tasso (Indian Farming, 2024)
Barbonymus gonionotus, also known as ‘Java Puti’ or ‘Silver Barb’, offers significant potential for expanding regional aquaculture. This freshwater fish, native to Southeast Asia, has shown impressive adaptability, rapid growth, and strong market demand, making it an attractive choice for cultivation in the cold climate of the Meghalaya hills in Northeast India. This article examines the fish's potential as a sustainable aquaculture species, focusing on its biological characteristics and nutritional value. It explores the aquaculture prospects, as well as the economic, nutritional, ecological, and socio-economic advantages of farming this species, while also addressing the challenges and considerations involved. Key insights are provided to aid in the successful integration of the fish into the aquaculture sector. The adoption of this species has the potential to enhance the diversity, resilience, and sustainability of aquaculture in the Meghalaya hills.